2021
DOI: 10.1021/acsaem.0c02472
|View full text |Cite
|
Sign up to set email alerts
|

Phosphine Oxide Derivative as a Passivating Agent to Enhance the Performance of Perovskite Solar Cells

Abstract: Defects of metal-halide perovskites detrimentally influence the optoelectronic properties of the thin film and, ultimately, the photovoltaic performance of perovskite solar cells (PSCs). Especially, defect-mediated nonradiative recombination that occurs at the perovskite interface significantly limits the power conversion efficiency (PCE) of PSCs. In this regard, interfacial engineering or surface treatment of perovskites has become a viable strategy for reducing the density of surface defects, thereby improvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 67 publications
(109 reference statements)
0
15
0
Order By: Relevance
“…38 The expedited crystallization gives rise to the rapid formation of perovskites within a short time, which is suggested to produce polycrystals with large grain sizes and reduced grain boundaries (Figures S1 and S2). 38 Combined with the well-established surface passivation by Lewis base, 39 it lends confidence that the surface defect states can be effectively diminished via the TU treatment. Nevertheless, it is also reported that swift crystallization is sometimes undesirable for the self-passivation of trap states, which results in more structural defects.…”
mentioning
confidence: 99%
“…38 The expedited crystallization gives rise to the rapid formation of perovskites within a short time, which is suggested to produce polycrystals with large grain sizes and reduced grain boundaries (Figures S1 and S2). 38 Combined with the well-established surface passivation by Lewis base, 39 it lends confidence that the surface defect states can be effectively diminished via the TU treatment. Nevertheless, it is also reported that swift crystallization is sometimes undesirable for the self-passivation of trap states, which results in more structural defects.…”
mentioning
confidence: 99%
“…Since metallic Pb 0 species in perovskites could act as detrimental non-radiative recombination sites, the addition of TPP molecules could enhance the photovoltaic performance and stability of the PSCs by passivating the undercoordinated Pb 2 + defects and reducing the number of metallic lead species. [42,43] In contrast, the Pb 0 peak is significantly suppressed in the TPP-passivated perovskite film. Figure 1c represents the P 2p 3/2 and P 2p 1/2 peaks corresponding to binding energies of 132.68 and 133.60 eV.…”
Section: Resultsmentioning
confidence: 97%
“…It is important to note that the pristine perovskite film reveals the presence of metallic lead (Pb 0 ) peaks at binding energies of 136.80 and 141.60 eV, which could be attributed to the chemical reaction between organic components and the adsorbed oxygen/moisture. Since metallic Pb 0 species in perovskites could act as detrimental non‐radiative recombination sites, the addition of TPP molecules could enhance the photovoltaic performance and stability of the PSCs by passivating the undercoordinated Pb 2+ defects and reducing the number of metallic lead species [42,43] . In contrast, the Pb 0 peak is significantly suppressed in the TPP‐passivated perovskite film.…”
Section: Resultsmentioning
confidence: 99%
“…One extended approach followed by many groups has succeeded in utilizing the interface engineering strategy to minimize the inuence of moisture and improve stability. [22][23][24][25] For that, many interfacial materials have been investigated, including metal oxides, 26 polymers, 27 and carbon-based materials. 28 As an example of this approach, the use of phenethylammonium iodide (PEAI) as a passivating agent, reduces the trap density (1.53 Â 10 15 cm À3 ) compared to the control sample (2.78 Â 10 15 cm À3 ).…”
Section: Introductionmentioning
confidence: 99%